Occupy and the Temporal Politics of Prefigurative Democracy - Kamilla Petrick (tripleC: Communication, Capitalism & Critique)
This article sheds new light on the Occupy movement by foregrounding its temporal dimensions, particularly in relation to a previous major cycle of transnational contention, the alter-globalization movement (AGM). The discussion engages three temporal considerations in particular: 1) the centrality of instantaneous digital media to both movements’ rapid rise and diffusion 2) the pervasiveness – especially within Occupy – of the temporal ethos of prefigurative politics, and 3) the sustainability and longer term legacy of the Occupy cycle, from the temporal vantage point of the year 2016, i.e. five years since the movement’s rise and prompt demise, and fifteen years since the peak of the AGM. The article’s conclusion insists on the importance of a long term vision when it comes to evaluating the outcomes of collective action.